PENGGUNAAN SISTEM INFORMASI GEOGRAFIS DALAM PENENTUAN KESESUAIAN LOKASI SARANA PENDIDIKAN MENENGAH DI KECAMATAN MIJEN - Iin Choirunnisa; Intan Muning Harjanti (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2021)
Mijen District based on Semarang City Regional Regulation Number 14 of 2011 concerning Spatial Planning for Semarang City 2011-2031 is one of the educational areas in Semarang City which is planned to further develop vocational education facilities into favorite educational facilities. Education is an important aspect in the development of people's lives because it is the basis for the development of a constructive and creative mindset. The population that continues to increase needs to be balanced with the optimization of the function of public service facilities, one of which is education. To make Mijen District have superior secondary education facilities, it is necessary to fulfill the need for education in Mijen District, one of which is by paying attention to the location of education. Location of educational facilities that are safe, comfortable, strategic, and easily accessible is one of the important factors that excellent educational facilities must have. Therefore, it is necessary to identify the suitability of the location for secondary education facilities in Mijen District by taking into account factors such as area function, disaster-prone, accessibility, and service coverage. This analysis uses quantitative research methods with geographic information system tools in the form of scoring, overlay and network analysis. Geographic information systems can be used to identify the suitability of the location of secondary education facilities. The application of geographic information systems supported by further studies such as identification of demand and availability of educational facilities as well as the hierarchy of services can play a role in determining the location of appropriate and targeted secondary education facilities.